氷板と晶氷が混在した橋脚部におけるアイスジャム氾濫実験 - 山田, 隆司; YAMADA, Ryuji; 吉川, 泰弘; ヨシカワ, ヤスヒロ; YOSHIKAWA, Yasuhiro; 小池, 太郎; KOIKE, Taro; 横山, 洋; YOKOYAMA, Hiroshi (土木学会, 2020)
本研究は，橋脚部におけるアイスジャム現象の解明のために，実河川の現象に近い氷板と晶氷が混在する実氷を用いたアイスジャム実験を実施した．晶氷の影響を明らかにするために，氷板模型速度と流下堆積枚数，高水敷での氾濫範囲，水位水深変動を用いて検討を行った．晶氷を含む場合は，流下する氷板の下に晶氷が堆積して氷同士が固着し大きな塊として流下し，形状抵抗が大きくなる．このため，氷板速度は遅くなり，流下堆積枚数が増加することが分かった．また，晶氷を含む場合は，大きな氷塊となって流下するため，アイスジャム発生後の上流での氾濫速度は速く，晶氷を含まない場合に比べて急激に氾濫することが推察された．最終的な上流での氾濫範囲は晶氷有り無しで同程度であった． This study aims to clarify the ice jam phenomenon around piers. We conducted an ice jam experiment which used mixed real ice with ice sheet and frazil slush. In order to clarify the effect of frazil slush, the experimental results show that ice velocity, number of ice, floods area variations, water level variations. In the case of containing frazil slush, they accumulate underneath the flowing ice sheet, sticking to each other and flowing down as large blocks. And, Ice sheet velocity is slowed down because the shape resistance increases. In the case of containing frazil slush, the ice flows downstream as large ice blocks. When ice jam is generated, the upstream floods area velocity increases and floods rapidly. journal article